Growth and physiological potential of various turf grass species under graded shade levels - SINGH, BABITA; SINDHU, S S; ARORA, AJAY; YADAV, HARENDRA (The Indian Journal of Agricultural Sciences, 2021)
An study was carried out to evaluate the effects of graded shade levels on the growth and quality of turf grass species Cynodon dactylon (Bermuda grass), Zoysia matrella (Manilla grass), Stenotaphrum secundatum (St. Augustine grass), Paspalum notatum (Bahia grass), Paspalum vaginatum (Seashore Paspalum), Dactyloctenium aegyptium (Crowfoot grass), Axonopus affinis (Mat grass/Carpet grass) and Eremochloa ophiuroides (Centipede grass). These species grown under shade nets with different shading intensity of 25%, 50%, and 75% along with control (without shade net) were investigated at Division of Floriculture and Landscaping, IARI, New Delhi during 2017-19. Among the all species, Crowfoot grass and Zoysia found good under reduced irradiance conditionas compared to open conditions, while, St. Augustine, Bahia and Seashore Paspalum performed well from 25-50% reduced irradiance level but these were best under open conditions. Performance of Bermuda grass, Carpet grass and Centipede were not satisfactory under reduced irradiance level.